Evaluation of normal appendix vermiformis in adults with multidetector computed tomography - Turkoglu, Huseyin; Onur, Mehmet Ruhi; Poyraz, Ahmet Kursad; Kocakoc, Ercan (Elsevier Science Inc, 2012)
To determine the utility of different contrast enhancement phases (unenhanced, arterial, and venous), slice thicknesses (0.5, 3, and 5 mm), and planes (axial and coronal) in the evaluation of appendix vermiformis (AV) on multidetector computed tomography (MDCT), CT examinations of 600 patients were obtained. No significant difference was found between the different imaging planes, slice thicknesses, and contrast enhancement phases in terms of detection rates of AV. The mean diameter of AV in the axial plane (5.93 +/- 0.06 mm) was significantly lower than that in the coronal plane (6.18 +/- 0.06 mm). Evaluation of AV on MDCT is enhanced by combined interpretation on axial and coronal planes. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Appendix; Multidetector computed tomography; Multiplanar reformation; Adults